Acoustic differentiation of dental soft and hard tissues using remote speckle-analysis during Er:YAG ablation - Lengenfelder, Benjamin; Schwarzkopf, Karen; Oetter, Nicolai; Mehari, Fanuel; Eschner, Eric; Klämpfl, Florian; Stelzle, Florian; Kesting, Marco Rainer; Zalevsky, Zeev; Schmidt, Michael (Opto-Acoustic Methods and Applications in Biophotonics IV; 110771L (2019), 2019)
The Er:YAG laser has gained significant interest in the field of oral surgery due to its high water absorptivity, precision and patient acceptance. However, its application is limited by the lack of a contact-free feedback system which would enable safe laser guidance. In this work, a potential new, robust feedback modality based on speckle-analysis is presented which detects the acoustic signals produced during laser surgery. Oral soft- and hard tissue samples are investigated ex-vivo for its differentiation capability using the speckle modality. This technique might help to broaden the clinical application of Er:YAG laser
Keywords: Laser surgery; Er:YAG laser; tissue differentiation

Arrangement for the benchmarking of in-situ process monitoring of topographical process signatures within the Laser Powder Bed Fusion process - Schwarzkopf, Karen; Eschner, Eric; Schmidt, Michael (Proceedings of the Lasers in Manufacturing (LiM), 2021)

Correlation of Spatter Quantity and Speed to Process Conditions in Laser Powder Bed Fusion of Metals - Eschner, Eric; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Production at the leading edge of technology, 2020)

Evaluation of a laser-based sensor for the diagnosis of neurological disorders - Tenner, Felix; Regensburger, Martin; Schramm, A; Söhle, Mona; Schwarzkopf, Karen; Zalevsky, Zeev; Schmidt, Michael (2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2017)
Keywords: biomedical equipment; biomedical measurement; laser applications in medicine; muscle; neurophysiology; optical sensors; patient diagnosis; involuntary muscle activity; laser-based sensor; neurological disorder diagnosis; neurological disorders; remote quantification; ultrasound measurements; whole body measurement; Measurement by laser beam; Muscles; Skin; Speckle; Transducers; Ultrasonic imaging; Ultrasonic variables measurement

Feature extraction based on scalable hypothesis tests from photodiode data in laser welding processes - Will, Thomas; Schwarzkopf, Karen; Hölbling, Claudio; Müller, Lars; Schmidt, Michael (Procedia CIRP, 2022)
Inline monitoring technologies gain increasing importance in industrial laser welding applications. Multiple sensing technologies can be implemented for classification of welding defects. Feature extraction from sensing data is a time-consuming process due to various algorithm possibilities for the identification of relevant features. Feature extraction based on scalable hypothesis tests (FRESH) allows for feature extraction with a combination of various time series characterization methods. FRESHs feature selection promises a quick extraction of relevant features from sensing data with an automatically configured hypothesis test. In the example of classification of spatter events, we show that FRESH can be used for the extraction of relevant features with photodiode sensing data in laser welding of copper.
CRIS-Team Scopus Importer:2022-11-25
Keywords: classification; copper; FRESH; laser welding; machine learning; photodiode; process control; process monitoring; spatter

Material Dependent Influence of Ring/Spot Beam Profiles in Laser Powder Bed Fusion - Chechik, Lev; Schwarzkopf, Karen; Rothfelder, Richard; Grünewald, Jonas; Schmidt, Michael (Additive Manufacturing Letters, 2024)
In recent years, the topic of beam shaping for improved laser material processing has rapidly grown influencing metal laser powder bed fusion (PBF-LB/M). Given the need to reduce the cost and improve control of the PBF-LB/M process to make it more competitive with traditional manufacturing methods, increasing productivity of PBF-LB/M is critical. When research reports a new beam profile (e.g. ring profile) to improve productivity on a specific material, it is often generalised, and assumed to have the capability to improve productivity in PBF-LB/M across the board. In this work, we use both low-fidelity simulations and experimental work to investigate the difference between Gaussian and ring/spot beam profiles on metals with very different thermal properties (a stainless steel and an aluminium alloy). We show that the two materials have opposite responses to the change in beam profile (both in terms of melt pool dimensions and thermal gradients); further, the most beneficial intensity distribution is dependent on the energy input to the material. This exemplifies yet another way in which the PBF-LB/M process is non-linear and contradicts the idea that a ring/spot laser profile is beneficial for all laser processing technologies. This highlights the need for further research into the non-linear effect of varying intensity distributions on laser processing before the benefits of dynamic beam shaping can be truly realised.<br
Keywords: Beam shaping; Additive manufacturing; Laser material processing

Observation of the melt dynamics during laser remote fusion cutting - Burger, Silvana; Dilger, Pablo; Schwarzkopf, Karen; Staudt, Tobias; Schmidt, Michael (Procedia CIRP, 2022)
Laser remote fusion cutting (RFC) offers a method for laser fusion cutting of metal sheets without need for a cutting gas. It is closely related to laser keyhole welding, which can transition into RFC for suitable parameters, such that the pressures in the process zone lead to a melt ejection on the bottom of the metal sheet. The mechanisms leading up to the melt expulsion are not fully understood yet and need further investigation. In this work, the cutting front is observed through a borosilicate glass sheet using a high-speed imaging system. In the setup, the glass sheet and a sample metal sheet are clamped together and the process zone is set directly at the interface between metal and glass. This setup allows for the observation of the melt dynamics adjacent to the glass sheet. In the experiments, the keyhole formation and the cutting front are investigated using a 6 kW disk laser and different feed velocities for cutting.<br

Revealing the influence of ring-shaped beam profiles in high-speed laser beam microwelding by synchrotron x-ray imaging - Schwarzkopf, Karen; Burger, Silvana; Chechik, Lova; Forster, Carola; Döring, Markus; Spurk, Christoph; Hummel, Marc; Olowinsky, Alexander; Beckmann, Felix; Moosmann, Julian; Schmidt, Michael (Journal of Laser Applications, 2024)
Laser beam microwelding is a precise technique for joining miniature metal components with high feed rates, which is crucial for productivity. However, high feed rates provoke humping formation—periodic beadlike protuberances along the weld seam—that compromise weld integrity. While humping has been associated with the keyhole transition from a narrow to an elongated shape using standard laser intensity distributions (e.g., Gaussian, top-hat), the impact of complex beam profiles, like ring-shaped intensity distributions, remains less understood. In this work, the influence of core-only, ring-only, and superimposed core-ring intensity distributions on humping formation during laser beam microwelding is investigated by means of synchrotron x-ray imaging. Single-track experiments on stainless steel (1.4404) at 1000 mm/s reveal that the keyhole geometry shifts from deep and narrow with core-only power input to shallow and elongated with ring-only power input. Using a superimposed core-ring intensity distribution (Pc = 300 W, Pr = 600 W) results in a U-shaped capillary and the reduction of the humping amplitude by nearly 80% (from 45.61 μm with core-only to 10.29 μm). The additional laser power comes with the tripling of the melt pool width (from 81 μm with core-only to 263 μm) likely decreasing the melt flow velocity. The reduced variability of the capillary length present for the superimposed intensity distribution further indicates a stabilized evaporation behavior. This work provides valuable insights into mitigating humping formation during laser beam microwelding of stainless steel at elevated feed rates using core-ring intensity distributions.<br

Shedding Light on Gas-Dynamic Effects in Laser Beam Fusion Cutting: The Potential of Background-Oriented Schlieren Imaging (BOS) - Burger, Silvana; Schwarzkopf, Karen; Klämpfl, Florian; Schmidt, Michael (Sensors, 2023)
In laser beam fusion cutting of metals, the interaction of the gas jet with the melt determines the dynamics of the melt extrusion and the quality of the resulting cutting kerf. The gas-dynamic phenomena occurring during laser beam cutting are not fully known, especially regarding temporal fluctuations in the gas jet. The observation of gas and melt dynamics is difficult because the gas flow is not directly visible in video recordings and access to the process zone for observation is limited. In this study, the problem of imaging the gas jet from the cutting nozzle is addressed in a novel way by utilizing the striation pattern formed at the cutting kerf as a background pattern for background-oriented Schlieren imaging (BOS). In this first feasibility study, jets of different gas nozzles were observed in front of a solidified cutting kerf, which served as a background pattern for imaging. The results show that imaging of the characteristic shock diamonds of cutting nozzles is possible. Furthermore, the resulting shock fronts from an interaction of the gas jet with a model of a cutting front can be observed. The possibility of high-speed BOS with the proposed method is shown, which could be suitable to extend the knowledge of gas-dynamic phenomena in laser beam fusion cutting.<br
Keywords: laser beam fusion cutting; laser material processing; process observation; high-speed imaging; Schlieren imaging; background-oriented schlieren (BOS); gas dynamics; gas jets; shock diamonds

Two-Color-Thermography for Temperature Determination in Laser Beam Welding of Low-Melting Materials - Schwarzkopf, Karen; Rothfelder, Richard; Rasch, Michael; Schmidt, Michael (Sensors, 2023)
Spatial and temporal knowledge of temperature evolution is crucial in laser beam welding of low-melting materials such as aluminum alloys. Current temperature measurements are restricted to (i) one-dimensional temperature information (e.g., ratio-pyrometers), (ii) a priori knowledge of emissivity (e.g., thermography), and (iii) high-temperature regions (e.g., two-color-thermography). This study presents a ratio-based two-color-thermography system that enables acquiring spatially and temporally resolved temperature information for low-melting temperature ranges (<1200 K). The study demonstrates that temperature can be accurately determined despite variations in signal intensity and emissivity for objects emitting constant thermal radiation. The two-color-thermography system is further transferred into a commercial laser beam welding set-up. Experiments with varying process parameters are conducted, and the ability of the thermal imaging method to measure dynamic temperature behavior is assessed. Image artifacts presumably caused by internal reflections inside the optical beam path limit the direct application of the developed two-color-thermography system during dynamic temperature evolution.<br

Understanding the thermo-fluid-microstructural impact of beam shaping in Laser Powder Bed Fusion using high-fidelity multiphysics simulation - Bayat, Mohamad; Zinovieva, Olga; Zinoviev, Aleksandr; Rothfelder, Richard; Schwarzkopf, Karen; Schmidt, Michael; Hattel, Jesper H. (Procedia CIRP, 2024)
Beam shaping of lasers is a topic that has received relatively less attention in the context of metal additive manufacturing (MAM) processes. This technique allows for modulation or spatial alternation of the intensity profile of the laser. As the bulk of the work within MAM primarily revolves around Gaussian beam profiles, the precise impact and potential of other beam shapes is still an unanswered question. In this work a multiphysics numerical model of the laser powder bed fusion (LPBF) process of Ti6Al4V without powder is developed and the model can predict thermofluid-microstructural conditions. The model predictions are compared with experimental data from single-Track specimens, and the comparison shows a very good agreement. It is shown that the ring spot beam profile (RSBP) results in substantially wider melt pools as compared to the ones forming using the Gaussian beam profile (GBP). The microstructural predictions show that for GBP the grains converge to the center line of the melt pool, while for ring beam profile (RBP), the grains tend to converge to a single point. Finally, the impact of different ring radii for RBP is studied and the results show that at larger ring radii, a noticeable bulge of liquid metal forms right beneath the laser beam.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Beam shaping; computational fluid dynamics; laser powder bed fusion; microstructural simulation; multiphysics simulation